Synthesis of novel benzothiazole amides: Evaluation of PPAR activity and anti-proliferative effects in paraganglioma, pancreatic and colorectal cancer cell lines. Issue 16 (15th August 2019) - Ammazzalorso, Alessandra; De Lellis, Laura; Florio, Rosalba; Laghezza, Antonio; De Filippis, Barbara; Fantacuzzi, Marialuigia; Giampietro, Letizia; Maccallini, Cristina; Tortorella, Paolo; Veschi, Serena; Loiodice, Fulvio; Cama, Alessandro; et al.
Graphical abstract: Highlights: A series of benzothiazole amides were synthesized and tested toward PPARs. Novel compounds induced a marked anti-proliferative activity in paraganglioma. Derivative 2b markedly impaired colony formation capacity in paraganglioma cells. Abstract: The reduced activation of PPARs has a positive impact on cancer cell growth and viability in multiple preclinical tumor models, suggesting a new therapeutic potential for PPAR antagonists. In the present study, the benzothiazole amides 2a-g were synthesized and their activities on PPARs were investigated. Transactivation assay showed a moderate activity of the novel compounds as PPARα antagonists. Notably, in cellular assays they exhibited cytotoxicity in pancreatic, colorectal and paraganglioma cancer cells overexpressing PPARα. In particular, compound 2b showed the most remarkable inhibition of viability (greater than 90%) in two paraganglioma cell lines, with IC50 values in the low micromolar range. In addition, 2b markedly impaired colony formation capacity in the same cells. Taken together, these results show a relevant anti-proliferative potential of compound 2b, which appears particularly effective in paraganglioma, a rare tumor poorly responsive to chemotherapy.